PENGENALAN DAN IMPLEMENTASI UI/UX DAN PEMROGRAMAN WEB DASAR PADA SISWA SEKOLAH MENENGAH PERTAMA (Studi Kasus: SMPN 3 PAGEDANGAN) - Agus Rahmawan; Alva Herbart Miftahul Firdaus; Dimas Adiansyah; Fauzan Kholid; Maulana Sandy; Mochamad Masdarul Anwar; Muhammad Bintang; Rafi Ivan Alessandro; Samsul Maarif; Syech; Galuh Saputri (Abdi Jurnal Publikasi, 2024)
Community service is an integral part of the Tridharma of Higher Education, aimed at making a tangible contribution to society. This activity was carried out at SMPN 3 Pagedangan under the theme "Introduction and Implementation of UI/UX and Basic Web Programming." The program aimed to enhance students' digital literacy as preparation for navigating the increasingly advanced technological era. The methods implemented in this program included material delivery, interactive discussions, and practical sessions. Students were introduced to fundamental concepts of User Interface (UI) and User Experience (UX) design, such as visual hierarchy and navigation, as well as basic web programming using HTML and CSS. The results demonstrated that students successfully grasped the basic concepts of UI/UX and applied basic programming skills to create simple web page structures. Furthermore, the program enhanced students' critical thinking, logical reasoning, and creativity. However, challenges such as limited time and resources affected the optimization of the outcomes. This program is expected to serve as an initial step in preparing a young generation with strong digital literacy skills, capable of adapting to technological challenges in the future. The findings highlight the need for adequate infrastructure support and more structured planning to ensure the sustainability of similar programs.